The social dimension of the reform of the sugar market in the European Union (based on the example of Poland) - Anna Dubownik (Journal of Geography, Politics and Society, 2015)
The study is an attempt to determine the consequences of the reform of the sugar market in the European Union (2006-2010) for small towns which were affected by liquidation of sugar beets foot-processing plants. This multifaceted research problem, apart from producers and growers, also concerns local communities often from small towns and in some cases also villages. Despite the fact that this first reform of the Polish sugar market has already finished, its consequences for the local development and the level of social capital are still difficult to grasp.